PBDEs, PCBs and organochlorine pesticides distribution in edible fish from Negro River basin, Argentinean Patagonia - Ondarza, Paola Mariana (2014)
DDTs, endosulfans, HCHs, chlordanes, PCBs and PBDEs levels were determined in different tissues of patagonian silverside (Odontesthes hatcheri) from the Upper (UV), Middle (MV) and Lower (LV) valleys of the Negro River, Argentina. Results showed a direct relation between pollutant levels in fish and land uses along the basin. All tissues showed decreasing levels from headwaters (UV) to downstream (LV). A significant predominance of organochlorine pesticides (306–3449 ng g−1 lipid) followed by ΣPCBs (65–3102 ng g−1 lipid) and ΣPBDEs (22–870 ng g−1 lipid) was observed in all tissues and valleys, suggesting agriculture as the main source of pollutants in this basin. Pesticides were dominated by DDTs (90% pp′-DDE) followed by endosulfan (α- > β- > sulfate), γ-HCH and γ-chlordane showing the prevalence of legacy compounds. Endosulfan levels point out the current use of technical endosulfan in the surrounding areas. The highest PCBs and PBDEs concentrations observed in fish from UV were associated to hydroelectric power plants and industries established upstream. PCB fingerprint presented a prevailing contribution of hexa-CBs (66 ± 7%) and penta-CBs (27 ± 9%), with a similar composition to Aroclor 1254–1260. The predominance of BDE-47 (69 ± 17%) among PBDEs, followed by BDE-100 and BDE-99, suggests possible debromination processes. These results were similar to worldwide trends found in fishes and environmental compartments. PCBs levels in silverside muscles along the Negro River exceeded the maximum limits for safe consumption, suggesting a possible human health risk related to silverside ingest. Therefore, a continued long-term monitoring of organic contaminants in fishes is needed in order to assess the potential risk for human health.